Memorandum of Understanding regarding mutual assistance and co-operation for the prevention and repression of customs offenses in the Caribbean zone ([s.n.] [S.l.])
Sets out terms of assistance to be provided between Caribbean Customs Administrations in order to prevent and repress customs offenses in the region.
Unpublished